2012
DOI: 10.1007/s00442-012-2362-4
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime offspring production in relation to breeding lifespan, attractiveness, and mating status in male collared flycatchers

Abstract: As a comprehensive fitness parameter, lifetime reproductive success (LRS) is influenced by many different environmental and genetic factors, among which longevity is one of the most important. These factors can be reflected in secondary sexual characters, which may affect the life histories of individuals via social relations with conspecifics. Facultative polygyny in birds is another conspicuous reproductive trait that potentially increases male reproductive success, but lifetime success data in relation to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
16
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 49 publications
5
16
1
Order By: Relevance
“…On the other hand, our results are in agreement with those of earlier studies performed in this population, suggesting that this trait is a poor indicator of genetic or phenotypic quality in our birds (Garamszegi et al 2006;Hegyi et al 2002Hegyi et al , 2006Hegyi et al , 2007Hargitai et al 2012; but see Hegyi et al 2011, Markó et al 2011. Furthermore, in a recent long-term study we showed that forehead patch size did not predict lifetime offspring recruitment (Herényi et al 2012). We can assume that the advantages of large forehead patch may appear in other processes of sexual selection, such as extra-pair paternity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…On the other hand, our results are in agreement with those of earlier studies performed in this population, suggesting that this trait is a poor indicator of genetic or phenotypic quality in our birds (Garamszegi et al 2006;Hegyi et al 2002Hegyi et al , 2006Hegyi et al , 2007Hargitai et al 2012; but see Hegyi et al 2011, Markó et al 2011. Furthermore, in a recent long-term study we showed that forehead patch size did not predict lifetime offspring recruitment (Herényi et al 2012). We can assume that the advantages of large forehead patch may appear in other processes of sexual selection, such as extra-pair paternity.…”
Section: Discussionsupporting
confidence: 91%
“…In facultatively polygynous species, males can also increase their reproductive output by acquiring a second female. However, in birds, the advantage of polygynous males is not so obvious when considering the recruitment rate of offspring to the breeding population (Lubjuhn et al 2000;Pribil 2000;Herényi et al 2012). Males cannot feed two broods at the same intensity as only one brood, which results in lower fledging condition at least in the secondary brood of polygynous males.…”
Section: Introductionmentioning
confidence: 99%
“…The Collared Flycatcher is a long-distance migratory, insectivorous passerine. This species is predominantly monogamous (Garamszegi et al 2004b;Herényi et al 2010), and females usually lay five to seven eggs of one clutch per breeding season (Török et al 2004). Collared Flycatcher eggs appear light blue-green in the human visible spectrum, and have a peak of reflectance at 490 nm at the visible spectrum, and at 320 nm at UV wavelengths (Hargitai et al 2008).…”
Section: Study Species and Field Proceduresmentioning
confidence: 99%
“…Collared Flycatcher Ficedula albicollis (Herényi et al . ) or Long‐tailed Tit Aegithalos caudatus (MacColl & Hatchwell ), and others identifying circumstances where body size appears to influence LRS. For example, Murphy () found that smaller female Eastern Kingbirds Tyrannus tyrannus produced more offspring during their lifetime, which he attributed to lower maintenance costs and more efficient use of available energy resources.…”
Section: Discussionmentioning
confidence: 99%